Quercetin Protects Hepatocyte from Ferroptosis by Depressing Mitochondria-reticulum Interaction Through PERK Downregulation in Alcoholic Liver (P06-056-19). (13th June 2019) - Guo, Xiaoping; Lin, Hongkun; Liu, Jingjing; Yao, Ping
Abstract: Objectives: Considering the disorder of lipid metabolism and iron deposition in alcoholic liver (ALD), ferroptosis may play a vital role in its pathogenesis. In the present research, we sought to determine whether ferroptosis occurred in ALD and is associated with increased mitochondria-endoplasmic reticulum interaction (MAMs) through RNA-dependent protein kinase like ER kinase (PERK) upregulation and whether quercetin plays a role in ferroptosis. Methods: Our preliminary results temporarily focused on animals model. Adult male C57BL/6 J mice were isocalorically pair-fed either a regular or ethanol-containing Lieber De Carli liquid diets (28% energy replacement) supplemented with quercetin (100 mg/kg.bw) or not for 12 weeks. Results: Serum alanine aminotransferase(ALT) and aspartate aminotransferase (AST) were indicators of liver damage. Compared with regular diet group, alcohol consumption resulted in increased ALT and AST, quercetin treatment reversed the abnormalities induced by ethanol. Oil Red Ostain, depleted GSH and increased MDA in liver suggested disrupted lipid metabolism and abnormal redox system in E group. Together with the increased liver total iron, liable iron pool iron and mRNA level of prostaglandin endoperoxide synthase 2 (ptgs2), these data indicated the occurrence of ferroptosis in ALD which reversed by quercetin. Electron microscope pictures showed increased MAMs in E group. Moreover, as a junction protein to maintain MAMs stability and a key sensor of the unfolded protein response, the level of PERKis unchanged in liver tissue but increased in MAMs in E group which decreased in the supplement of quercetin, which suggested upregulated PERK contributed to the increased MAMs in alcohol consumption. Increased Acyl-CoA synthetase long-chain family member 4 (ASCL4) also observed in MAMs in E. Since ACSL4 mainly enriched in MAMs and is also a key protein involved in the execution of ferroptosis, it suggested increased MAMs in E group and correlation between ferroptosis and MAMs. Conclusions: Our results are preliminarily illustrated enhanced ferroptosis regulated by increased MAMs through PERK upregulation in ALD. And quercetin protected hepatocyte from ethanol toxicity by reversing above changes. Funding Sources: National Natural Science Foundation of China No. 81673164. Supporting Tables, Images and/or Graphs: